Lifestyle journalism - Hanusch, Folker, 1975- (Oxon : Routledge, 2013)
Lifestyle journalism has experienced enormous growth in the media over the past two decades, but scholars in the fields of journalism and communication studies have so far paid relatively little attention to a field that is still sometimes seen as "not real journalism". There is now an urgent need for in-depth exploration and contextualisation of this field, with its increasing relevance for 21st century consumer cultures. For the first time, this book presents a wide range of studies which have engaged with the field of lifestyle journalism in order to outline the various political, economic, social and cultural tensions within it. Taking a comparative view, the collection includes studies covering four continents, including countries such as Australia, China, Norway, Denmark, Singapore, the UK and the USA. While keeping the broader lifestyle field in mind, the chapters focus on a variety of sub-fields such as travel, music, food, health, fashion and personal technology journalism. This volume provides a fascinating account of the different facets of lifestyle journalism, and charts the way forward for a more sustained analysis of the field.
Keywords: Journalistiek ; lifestyle